The Role of Educators in the Formation of the Professional Character of Nursing Students: A Phenomenological Study - Edison Kabak; Isak JH. Tukayo (Indonesian Journal of Global Health Research, 2026)
This research focuses on the importance of the role of educators in shaping the professional character of nursing students, especially since this character is the basis for their readiness to face the demands of clinical practice. The purpose of this study is to explore students' experiences regarding how supervisors and lecturers affect the process of internalizing professional values. The study employed a phenomenological approach, involving ten students who underwent in-depth interviews to gain a more comprehensive understanding of their 10 experiences. The data analysis yielded five main themes: educator exemplars, mentoring in clinical simulations and practices, communication and team dynamics, affirmation of ethical values and professionalism, and challenges in applying professional character in real-life situations. The study's results indicate that the development of a professional character occurs through observation, direct guidance, intense interaction, and the inculcation of moral values by educators. In conclusion, educators play a crucial role in shaping students' professional identities, so that an exemplary and reflection-based learning approach needs to be strengthened in nursing education.